1992
DOI: 10.1155/1992/742635
|View full text |Cite
|
Sign up to set email alerts
|

Recognition Memory in Psychotic Patients

Abstract: Preliminary data are reported from experiments in which Warrington's (1984) Recognition Memory Tests were given to patients with misidentification delusions including the Capgras type and to psychotic patients. The results showed a profound impairment on face recognition for most groups, especially those with the Capgras delusion. It was rare to find a patent whose score on the word test was anything but normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
1
5
0
2
Order By: Relevance
“…A similar procedure is used with words, and was included here to check for general cognitive impairment. Ellis et al (1992) found a substantial impairment on the faces part of this test in a small group of Capgras patients.…”
Section: (B) Facial Identity Processingmentioning
confidence: 78%
“…A similar procedure is used with words, and was included here to check for general cognitive impairment. Ellis et al (1992) found a substantial impairment on the faces part of this test in a small group of Capgras patients.…”
Section: (B) Facial Identity Processingmentioning
confidence: 78%
“…There is already evidence to show that DMS subjects have face processing deficits which are demonstrable on face recognition tasks [42][43][44][45] and the as sociation with Charles Bonnet syndrome raises the possibility that visual pathway im pairment at the level of the eye may need to be investigated. There is no published study addressing this issue as far as we know.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do the present data fail to support Joseph's hy pothesis but if face recognition is exclusively a right hemisphere function one would not ex pect dual representations of familiar faces, one in each cerebral hemisphere. Given the results of Study l it is easy to make the prediction that CD patients will evince more problems than normal controls on face memory tasks [20]. In order to test this a group of 4 CD patients (3 of whom had tak en part in study 1) were given a test of unfa miliar face recognition that is commonly used in neuropsychological diagnosis [21].…”
Section: Studymentioning
confidence: 99%
“…To counter this possibility Ellis et al [20] also gave the WRMT faces task to 6 other psychotic patients matched as closely as possi ble to the CD group. Their median score was 44.0 -almost identical to the mean score for normal subjects shown in table 1, suggesting that being psychotic or receiving neuroleptic medication does not itself cause poor perfor mance on the WRMT faces task.…”
Section: Studymentioning
confidence: 99%